NOTARY ROLE IN ONLINE REGISTRATION IMPLEMENTATION OF FIDUCIARY GUARANTEE ON CREDIT AGREEMENTS - Zerlina Jihan Deavinsa; Mohamad Fajri Mekka Putra (Awang Long Law Review, 2022)
This study aims to determine the Notary's role toward creditors in the online registration of the Fiduciary Guarantee Deed and the Notary's responsibility if there is an error in the online registration of the Fiduciary Guarantee Deed. Empirical legal research is conducted in this study using a descriptive design that includes field and library research, utilizing a qualitative data analysis approach. The findings of this study suggest that notary play a significant role in people's lives, particularly when creating authentic deeds following statutory requirements. A notary is authorized by the Law on Notary Positions to create an authentic deed to provide legal protection and certainty. A notary's role is crucial in everyday transactions involving agreements, including those involving fiduciary guarantees. A notary's duties in the online registration of a fiduciary guarantee include creating the fiduciary guarantee deed and acting as the fiduciary recipient, or the person who accepts the creditor's power of attorney to register the fiduciary guarantee. The online Fiduciary Guarantee registration process is connected to 3 (three) different types of notary liability. Given their significant role in the online registration of fiduciary guarantees, notary must follow the precautionary principle to reduce the possibility of mistakes when preparing the deed and to register the fiduciary.